Strategi Guru Dalam Membentuk Akhlak Siswa Melalui Program Hafalan Al – Qur’an Juz 30 Dan Jurnal Harian Pada Mata Pelajaran Pai Di Masa Pandemik Covid-19 - Fikri Fadlurrahman; Iwan Hermawan; Kasja Eki Waluyo (Peneliti.net, 2022)
Education determines the development and realization of human resources, especially the development of the nation and state. Education has an important role in shaping human resources and a dignified nation's civilization will be achieved if it is able to educate the nation's life and is able to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative. , be independent and become a democratic and responsible citizen. In 2020, the whole world is experiencing an outbreak, namely the Covid-19 pandemic. The spread of the corona virus or Covid-19 in Indonesia has changed the teaching and learning process in schools. Therefore, in this study, the method used is qualitative research methods. This is used to find solutions so that students can still form their morals at school, as well as in the home environment. This research was conducted at SMPN 1 Karawang Barat. The findings or results obtained from this study are the satisfaction of parents of students and teachers at home and during the distance learning process. This program can be used in PAI subjects for students of SMPN 1 Karawang Barat